2001
DOI: 10.1046/j.1537-2995.2001.41020276.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of genomic DNA in plasma and serum samples: higher concentrations of genomic DNA found in serum than in plasma

Abstract: Most cell-free DNA in serum samples is generated during the process of clotting in the original collection tube. The concentration of cell-free genomic DNA in fresh plasma is probably the same as that in circulation. Consequently, while serum samples should not be used to monitor the concentration of cell-free DNA in a patient's circulation, serum collected from sample tubes containing clots (i.e., without anticoagulant), 3 to 5 days after the date of phlebotomy, could be useful as a source of DNA with which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
147
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(165 citation statements)
references
References 21 publications
16
147
0
2
Order By: Relevance
“…In addition, we were reassured by the results showing significantly more cell-free DNA in male sera compared with female sera, consistent with reports from other research groups (24). A study (27) pointed to finding more cell-free DNA in the serum in contrast to plasma due to lysis of white blood cells during centrifugation in the extraction step. The present study compared relative rather than absolute concentrations avoiding the white blood cell confounding factor.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we were reassured by the results showing significantly more cell-free DNA in male sera compared with female sera, consistent with reports from other research groups (24). A study (27) pointed to finding more cell-free DNA in the serum in contrast to plasma due to lysis of white blood cells during centrifugation in the extraction step. The present study compared relative rather than absolute concentrations avoiding the white blood cell confounding factor.…”
Section: Discussionsupporting
confidence: 89%
“…Two latter studies and their results were quite similar to our work, although our study differed in that we used fresh and frozen serum /plasma from the maternal blood of Haemophilia A carriers and we also used 2 pairs of primers for the SRY gene to obtain a reliable signal for fetal gender in a Real-Time duplex PCR analysis and finally, we used SYBR Green instead of a probe in this analysis. We were able to obtain a high degree of accuracy with fresh serum, rather than with plasma, which is consistence with several studies indicated that fetal DNA in serum is present in greater quantities than in plasma and its concentration increases some 100 times when samples are kept at 4°C for 4 to 5 days [36,37]. In case of the presence of the large amounts of non-target DNA which is the major problem related to amplifying low copy number DNA target sequences [38], we were well able to overcome this problem by combining duplex/ nested-PCR and LC-qPCR.…”
Section: Methodssupporting
confidence: 79%
“…Serum samples have been shown to contain cell free DNA generated during the clotting process by the in vitro lysis of white blood cells. 34 Also for samples obtained from melanoma patients, the method of blood processing has been shown to significantly affect the levels of circulating DNA extracted. 35 Our data comparing DNA yields from plasma and from serum in matched samples from healthy subjects indicated that higher levels are recovered from serum samples under our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%